2021
DOI: 10.1097/md.0000000000026931
|View full text |Cite
|
Sign up to set email alerts
|

Total vascular resistance, augmentation index, and augmentation pressure increase in patients with peripheral artery disease

Abstract: Peripheral arterial disease (PAD) is one of major vascular diseases which frequently coexists with coronary arterial disease and cerebrovascular disease. The patients with PAD have a poor prognosis when it progresses. A new blood pressure testing device enables to simultaneously measure brachial blood pressure (BP), central BP, and several vascular parameters, with easy and noninvasive, in a short time. Here, we aimed to evaluate these arterial stiffness parameters in patients with PAD.In this study, 243 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…High TVR is associated with mortality, heart failure, and cardiovascular events [38]. Another study utilizing the Mobil-O-Graph device reported a higher TVR in patients with peripheral arterial disease (PAD), which is atherosclerosis of the extremities and is associated with cardiovascular events [39]. While TVR did not show a significant increase in the hypertensive or non-dipping groups in the present study, the positive correlation between nocturnal TVR and albuminuria confirms its association with vascular disease.…”
Section: Discussionsupporting
confidence: 60%
“…High TVR is associated with mortality, heart failure, and cardiovascular events [38]. Another study utilizing the Mobil-O-Graph device reported a higher TVR in patients with peripheral arterial disease (PAD), which is atherosclerosis of the extremities and is associated with cardiovascular events [39]. While TVR did not show a significant increase in the hypertensive or non-dipping groups in the present study, the positive correlation between nocturnal TVR and albuminuria confirms its association with vascular disease.…”
Section: Discussionsupporting
confidence: 60%
“…High TVR is associated with mortality, heart failure, and cardiovascular events [24]. Another study utilizing the Mobil-O-Graph device reported a higher TVR in patients with peripheral arterial disease (PAD), which is atherosclerosis of the extremities and is associated with cardiovascular events [25]. While TVR did not show a signi cant increase in the hypertensive or non-dipping group in the present study, the positive correlation between nocturnal TVR and albuminuria con rms the association with vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have reported AIx to be an easy and reproducible parameter for indirect assessment of arterial stiffness. AIx is strongly correlated to direct measurements of arterial distensibility and can thereby be used as a surrogate for arterial stiffness ( Ng et al, 2006 ; Vlachopoulos et al, 2010 ; Takemoto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%